Acute cholangitis due to haemobilia complicating percutaneous cholecystostomy: First literature case report. (July 2022) - Beji, Hazem; Atri, Souhaib; Maghrebi, Houcine; Haddad, Anis; Makni, Amin; Kacem, Montasser
Abstract: Background: Laparoscopic cholecystectomy is the standard treatment for acute cholecystitis. Cholecystostomy is a good option in patients with significant comorbidities. We report a case of a patient having had a percutaneous cholecystostomy for acute cholecystitis complicated with haemobilia and acute cholangitis. Presentation of a case: A woman aged 64 years old, with a history of diabetes, arterial hypertension, and chronic obstructive pulmonary disease was admitted to our institution with acute cholecystitis. We opted for transhepatic percutaneous cholecystostomy (PC) and antibiotics. On the fourth day, the patient had acute cholangitis due to haemobilia. We injected physiologic saline serum through the drain of cholecystostomy to dissolve the blood clot. There was a clinical improvement. We performed laparoscopic cholecystectomy two months later. The patient had an uneventful recovery with a follow-up of five months. Discussion: We report the first literature report of acute cholangitis due to haemobilia complicating percutaneous cholecystostomy in a patient admitted for cholecystitis. We highlight the importance of the injection of saline physiologic serum from the catheter. Medical treatment with antibiotics may be enough knowing that blood clots can disappear spontaneously. In case of failure, ERCP with sphincterotomy should be performed. Conclusion: Haemobilia causing acute cholangitis is a rare complication of percutaneous cholecystostomy. Conservative treatment with antibiotics and injection of saline physiologic serum from the catheter is a good treatment option. In case of failure, ERCP should not be delayed. Highlights: Cholecystostomy for acute cholecystitis is a considerable option in comorbid patients. Acute cholangitis due to haemobilia is an extremely rare complication. Injection of physiologic serum saline from the drain is a conservative and efficient treatment. It facilitates the dissolution of blood clots.